Depressive Symptoms and Academic Performance in College: Do Personal Goals Play a Role? - Pare, Marie-Laurence; Marcotte, Diane (Canadian Journal of Counselling and Psychotherapy, 2022)
This study investigates the association between depressive symptoms and academic performance at the college level in Québec by examining personal goals as mediating variables. The sample consisted of 249 female and 148 male students at a Québec college. The Beck Depression Inventory (2nd ed.; Beck et al., 1996), an adaptation of the Personal Project Analysis (Little & Gee, 2007), and the R score (a standardized score used by Québec colleges) were used as measures. Regression analyses fail to support the existence of a direct link between more depressive symptoms and a lower R score. That said, analyses show an indirect association between both variables that is explained by a more negative appraisal of academic and career goals. Supports designed to help college students—who are in a period of identity exploration (Arnett, 2015)—develop a more positive appraisal of academic and career goals may protect such students from depression while fostering their academic success.